(untitled) (Medico Legal Update, 2021)
The study aims to find the relationship between COVID-19 virus infections and early births in women infected with this virus in of Al-Fallujah city. The prospective study was conducted in Al-Fallujah city during the period between February 1, 2020, and September 1, 2020, at Al-Fallujah Teaching Hospital. Through the study, 100 pregnant women were received, complaining of Covid-19 infections, which were diagnosed in Al-Fallujah, and now Real Time PCR was confirmed through nasopharyngeal swabs that were taken from Al-Fallujah Teaching Hospital. The study also included measuring the level of blood pressure, sugar andC-RP in those women during the fifth to eight week, where we were infected, and then in the 12th week of pregnancy took place, where communication was made, and a level was measured, and as a result, these women whocompleted the period with a pre-term labor, miscarriagebefore the 24th week of pregnancy or those completed the period with successful pregnancy. In this study, 33% of COVID-19 pregnant women were within the age group 24-30 years followed by 30% in the age group 31-38 year. In this study, 10 % of COVID-19 pregnant women suffer from hypertension, 13% were with Diabetes, 35% with UTI while 70% were suffered from fever.When reaching 24th week of pregnancy, and as shown in Table 3. The study showed that 40% COVID-19 pregnant women experienced completed the period with a pre-term labor, 10% was with miscarriagebefore the 24thweek of pregnancy, while 50% of them completed the period continued the pregnancy. In this study, 82.5 % of COVID-19 pregnant women with preterm labor were suffered previously from fever comparing with 55% of COVID-19 pregnant women without preterm labor. The study showed the highest mean of C-reactive protein was present COVID-19 pregnant women with preterm labor (22.5±2.14 mg/ml), fan lowest mean was in women who without preterm labor (14.6±2.11 mg/ml) (P<0.01). Conclusions: The study showed a significant relation ofCOVID-19 infection with pregnant women who pre-term labor especially who have high body temperature.